Leading Trauma-Informed Education Practice as an Instructional Model for Teaching and Learning - Stokes, Helen (Frontiers in Education, 2022)
Advances in trauma-informed practices have helped both researchers and educators understand how childhood trauma impacts the developmental capacities required for successful learning within school. However, more investigation is required to understand how leaders can implement trauma-informed practices in targeted areas of their schools. This paper is a case study of one school who intentionally implemented a trauma-informed instructional practice approach after undertaking trauma informed positive education professional learning over a period of two and a half years. The research was guided by three questions: how are students supported in their learning and wellbeing; how can teachers be supported to develop consistent trauma-informed practice in their classrooms; and what is the role of leadership in this process? To research the approach, quantitative measures of staff and student perceptions and qualitative strategies centring the voices and experiences of students, teachers, and school leaders, were employed. Implications for school leaders suggest that when implemented as a whole-school approach through multiple and simultaneous mechanisms, trauma-informed positive education instructional practices have the possibilities of yielding enhanced outcomes for wellbeing and enable students to be ready to learn.